The infusion of menthol into the esophagus evokes cold sensations in healthy subjects but induces heartburn in patients with gastroesophageal reflux disease (GERD). Issue 11 (25th April 2019) - Banovcin, Peter; Duricek, Martin; Zatko, Tomas; Liptak, Peter; Hyrdel, Rudolf; Kollarik, Marian
SUMMARY: Recent studies in animal models have reported that some afferent fibers innervating the esophagus express the cold receptor TRPM8. In the somatosensory system the stimulation of TRPM8 leads to cold sensations and in certain circumstances alleviates pain. It is therefore hypothesized in this paper that the esophageal infusion of the TRPM8 activator menthol evokes cold sensations from the esophagus and alleviates heartburn in humans. The esophageal infusion of menthol (3 mM, 20 min) evoked cold sensations in 11 of 12 healthy subjects. In striking contrast, the esophageal infusion of menthol evoked heartburn in 10 of 10 patients with gastroesophageal reflux disease (GERD). In healthy subjects the cold sensation evoked by menthol was perceived only as a minor discomfort as evaluated by the visual analog scale (VAS score 1.9 ± 0.3 on the scale 1–10). However, in patients with GERD the menthol-induced heartburn was perceived as painful (VAS score 5.6 ± 0.6, P < 0.01 compared to healthy subjects). It is concluded that the sensations evoked by esophageal infusion of menthol change from relatively nonpainful cold sensations in healthy subjects to painful heartburn sensations in patients with GERD. These qualitative and quantitative changes indicate substantial alterations in afferent signaling mediating sensations from the esophagus in patients with GERD.